2017
DOI: 10.1071/an16257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo injected prebiotics and synbiotics on the caecal fermentation and intestinal morphology of broiler chickens

Abstract: Manipulations of the intestinal microbiota composition may improve the health and performance of chickens. In ovo technology allows the administration of a bioactive substance to enter directly into the incubating egg. The objective of the present study was to investigate the effect of in ovo administered prebiotics or synbiotics on microbial activity products in the caeca and the development of the small intestine of broiler chickens. Ross 308 male chickens hatched from eggs injected in ovo with prebiotics or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In this study, IOI of naringin in 30 mg increased the weight of recently hatched chickens by stimulating the development of the chick embryo. This is in agreement with other studies in terms of IOI of prebiotic and synbiotic (Miśta et al, 2016), carbohydrates (Ferket & Uni, 2001), and amino acids or antioxidant (El-Senousey et al, 2017).…”
Section: Hatched Chickssupporting
confidence: 93%
“…In this study, IOI of naringin in 30 mg increased the weight of recently hatched chickens by stimulating the development of the chick embryo. This is in agreement with other studies in terms of IOI of prebiotic and synbiotic (Miśta et al, 2016), carbohydrates (Ferket & Uni, 2001), and amino acids or antioxidant (El-Senousey et al, 2017).…”
Section: Hatched Chickssupporting
confidence: 93%
“…Slawinska et al assured that synbiotics could significantly enhance the gene expression of interleukin‐4 (Th2) and interleukin‐6 (pro‐inflammatory) in the spleen, thereby stimulating B cell proliferation and synthesis of immunoglobulin. The study of Miśta et al concluded that the in ovo administration of synbiotics may be a more practical method to boost BW of broilers, ameliorate the short‐chain fatty acids of caecal profile, and enhance the villus length. In ovo (intra‐amniotic) feeding of synbiotic (inulin and Enterococcus faecium ) did not affect the percentage of hatchability and hatching weight of the chicks.…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
“…The villi surface area was also observed to increase post intra-amniotic administration of raffinose and stachyose [ 41 , 46 ], chickpea and lentil prebiotics [ 42 ], egg white peptides [ 42 ], symbiotic (inulin, Enterococcus faecium ) [ 48 ], mannan oligosaccharides [ 56 ], carbohydrates (dextrin, maltose, sucrose) [ 57 ], and zinc-methionine [ 58 ]. However, in ovo injected probiotics (inulin, transgalactooligosaccharides, Lactococcus lactis ) did not affect the villi heights, but rather changed the crypts’ depth [ 49 ]. The crypts’ depth increased after the injection of inulin combined with Enterococcus faecium [ 48 ] and mannan oligosaccharides [ 56 ], while the crypts’ depth was not affected by the injection of raffinose [ 46 ].…”
Section: In Ovo Administration and Small Intestinal Morphologymentioning
confidence: 99%
“…Interestingly, the SCFA proportions varied over time in that study. The acetate molar proportion decreased, while the propionate and butyrate proportion increased [ 49 ]. Calik et al (2016) used an approach that combined intra-amniotic with dietary administration to evaluate the effect of inulin with Enterococcus faecium on the SCFA composition [ 48 ].…”
Section: In Ovo Administration and Small Intestinal Morphologymentioning
confidence: 99%